2016
DOI: 10.1016/j.bmcl.2016.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Isatin derivatives with activity against apoptosis-resistant cancer cells

Abstract: In a search of small molecules active against apoptosis-resistant cancer cells, a series of isatin-based heterocyclic compounds were synthesized and found to inhibit proliferation of cancer cell lines resistant to apoptosis. The synthesis of these compounds involved a condensation of commercially available, active methylene heterocycles with isatin proceeding in moderate to excellent yields. The heterocyclic scaffolds prepared in the current investigation appear to be a useful starting point for the developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…In line with this, Rana and colleagues have shown that isatin-derived spirocyclic a-methylene-g-butyrolactone can be used as a novel anticancer agent [43]. Furthermore, a series of isatin-based heterocyclic compounds were found to inhibit proliferation of cancer cell lines resistant to apoptosis [44]. In the current study, we elucidated the molecular mechanism of their function and demonstrated that these small molecule activators of p53 operated via blunting the interaction between p53 and Mdm2.…”
Section: Introductionsupporting
confidence: 62%
“…In line with this, Rana and colleagues have shown that isatin-derived spirocyclic a-methylene-g-butyrolactone can be used as a novel anticancer agent [43]. Furthermore, a series of isatin-based heterocyclic compounds were found to inhibit proliferation of cancer cell lines resistant to apoptosis [44]. In the current study, we elucidated the molecular mechanism of their function and demonstrated that these small molecule activators of p53 operated via blunting the interaction between p53 and Mdm2.…”
Section: Introductionsupporting
confidence: 62%
“…The anticancer SAR of compounds 18 (IC 50 : 3.2 to >100 μM, MTT assay) and 19 (IC 50 : 3.9–44.6 μM) against apoptosis‐resistant U373 glioblastoma, A549 non‐small‐cell lung cancer, SKMEL‐28 melanoma, OE21 esophageal cancer along with apoptosis sensitive cells, including HS683 glioma, B16F10 murine melanoma, MCF‐7 breast cancer, and PC‐3 prostate cancer revealed that introduction of halogen atoms into the C‐7 position of isatin moiety could not improve the activity apparently. [ 58 ] The oxime at the C‐3 position was favorable to the activity, and compounds with oxime were more potent than the corresponding ketone analogs. Compound 19d (IC 50 : 3.9–13.9 μM) was active against all tested apoptosis‐resistant and sensitive cancer cell lines, but the activity was far lower than that of the reference β‐lapachone (IC 50 : <0.01–0.8 μM).…”
Section: Anticancer Activitymentioning
confidence: 99%
“…The biological data used in this study was the anti-cancer activity against MCF7, (in terms of -log IC 50 ), of a set of 109 isatin derivatives [43][44][45][46][47][48][49][50][51]. The data set was classified into calibration and prediction set by kenardston algorithm of the 20 prediction molecules from the spaces of the calculated descriptors.…”
Section: Data Setmentioning
confidence: 99%